Self-consistent long-time simulation of chirping and beating energetic particle modes in JT-60U plasmas. (8th December 2016) - Bierwage, A.; Shinohara, K.; Todo, Y.; Aiba, N.; Ishikawa, M.; Matsunaga, G.; Takechi, M.; Yagi, M.
Abstract: Recurring bursts of chirping Alfvén modes that were observed in JT-60U tokamak plasmas driven by negative-ion-based neutral beams (N-NB) are reproduced in first-principle simulations performed with an extended version of the hybrid code MEGA. This code simulates the interactions between gyrokinetic fast ions and magnetohydrodynamic (MHD) modes in the presence of a realistic fast ion source and collisions, so that it self-consistently captures dynamics across a wide range of time scales (0.01–100 ms). The simulation confirms that the experimentally observed phenomena known as 'fast frequency sweeping (fast FS) modes' are caused by bursts of energetic particle modes (EPM) with dominant toroidal mode number n = 1. On the long time scale (1–10 ms), the simulation reproduces the chirping range (40–60 kHz), the burst duration (few ms) and intervals (5–10 ms). On the short time scale (0.01–0.1 ms), it reproduces pulsations and phase jumps, which we interpret as the result of beating between multiple resonant wave packets. Having reproduced at multiple levels of detail the dynamics of low-amplitude long-wavelength Alfvén modes driven by N-NB ions, the next goal is to reproduce and explain abrupt large-amplitude events (ALE) that were seen in the same experiments at longer time intervals (10–100 ms).